Fuzzy Power Converter for Smart Shopping Cart - Jadhav, Komal; Awati, J. S.; Kumbhar, M. S. (Journal of Electronic Design Engineering, 2023)
Nowadays, the use of barcode for products presents several limitations, it requires a line of sight, has a low range and have less security. In our project, we proposed a system in which Radio Frequency Identification (RFID) technology is used. This system gives a solution to reduce the shopping time at supermarkets. Shopping trolleys are used by every supermarket to assist shoppers in choosing the items they want to buy. Customers may experience a variety of issues at the billing counter, such as waiting and not knowing if they have enough money to pay for the goods they have chosen. In addition to taking a lot of time, the counter-billing process requires additional staff. We have put up a method to address this issue, which makes use of a smart shopping cart to get around these obstacles. The NODEMCU, RFID Reader Module, RFID tags, LCD, and push buttons are all necessary for the hardware.